Associations Between Incarcerated Fathers' Cumulative Childhood Risk and Contact With Their Children. (April 2017) - Galardi, Tasha R.; Settersten, Richard A.; Vuchinich, Samuel; Richards, Leslie
Incarcerated fathers often experience early life risk factors that cumulate over time and are compounded by the negative repercussions of imprisonment. These dynamics may contribute to the intergenerational transmission of risk and help explain the persistent link between paternal incarceration and poor child outcomes. Contact between incarcerated fathers and their children can benefit them both, but there is limited research on the factors that affect father–child contact. Using data from the 2004 Survey of Inmates in State Correctional Facilities and a sample of fathers with at least one minor child ( N = 5, 809), the authors found that incarcerated fathers who experienced more childhood risk factors had less frequent contact with their children. A variety of inmate characteristics were also significant predictors of father–child contact. Parenting interventions could address incarcerated fathers' childhood risk experiences, which likely undermine the development and maintenance of family relationships, to help them develop prosocial skills.